Propuesta de mejora del nivel de servicio de la empresa SRH S.A.C. basado en la utilización de Lean Manufacturing, PMP y punto de reorden - Guzman Ascue, Marco Antonio (2021)
The main objective of this improvement proposal is to diagnose the current status of Servicio Revolucionario Hospitalario (SRH S.A.C.) business, an industrial laundry specialized in the renting service of hospital clothing, and propose viable solutions to the hospital clothing supply deficit, which is the main issue that affects the level service of the company, that currently is 85,56%. In the first place, a problem tree was used to identify the root causes of the main problem and at the same time, identify the consequences that will keep on if the main problem is not solved. After identify the causes that affect the level service, it was evidenced that 65,38% of the problem is due to the bad management at supplies purchase and the lack of production orders in hospitals, since they directly affect the decision-making in production planification of the supply of hospital clothings in health centers. In order to solve the problem, it was determined that the implementation of Visual management, Master Production Schedule and a supplies replenishment program based on reorder point are the best options, due to they allow to forecast the demand and the minimum stock for the order point. This will directly affect to the root cause. Finally, it was determined that the improvement proposal is economically viable with a VAN of S/ 1 877,48 and a TIR of 8,7842%, which is higher than the monthly COK of 1,5475%, in addition of increasing the service level to 92,77%, reaching the strategic objective of the company.